Two in one: use of divalent manganese ions as both cross-linking and MRI contrast agent for intrathecal injection of hydrogel-embedded stem cells - Kalkowski, Lukasz; Golubczyk, Dominika; Kwiatkowska, Joanna; Holak, Piotr; Milewska, Kamila; Janowski, Miroslaw; Oliveira, Joaquim M.; Walczak, Piotr; Malysz-Cymborska, Izabela (Pharmaceutics, 2021)
Cell therapy is a promising tool for treating central nervous system (CNS) disorders; though, the translational efforts are plagued by ineffective delivery methods. Due to the large contact surface with CNS and relatively easy access, the intrathecal route of administration is attractive in extensive or global diseases such as stroke or amyotrophic lateral sclerosis (ALS). However, the precision and efficacy of this approach are still a challenge. Hydrogels were introduced to minimize cell sedimentation and improve cell viability. At the same time, contrast agents were integrated to allow image-guided injection. Here, we report using manganese ions (Mn 2+ ) as a dual agent for cross-linking alginate-based hydrogels and magnetic resonance imaging (MRI). We performed in vitro studies to test the Mn 2+ alginate hydrogel formulations for biocompatibility, injectability, MRI signal retention time, and effect on cell viability. The selected formulation was injected intrathecally into pigs under MRI control. The biocompatibility test showed a lack of immune response, and cells suspended in the hydrogel showed greater viability than monolayer culture. Moreover, Mn 2+ -labeled hydrogel produced a strong T1 MRI signal, which enabled MRI-guided procedure. We confirmed the utility of Mn 2+ alginate hydrogel as a carrier for cells in large animals and a contrast agent at the same time. This research was funded by The National Centre for Research and Development, grant number 12/EuroNanoMed/2016.